2014
DOI: 10.1039/c4sc00484a
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating HIV gp120-ligand recognition through computationally-driven optimization of antibody-recruiting molecules

Abstract: Here we report on the structure-based optimization of antibody-recruiting molecules targeting HIV gp120 (ARM-H). These studies have leveraged a combination of medicinal chemistry, biochemical and cellular assay analysis, and computation. Our findings have afforded an optimized analog of ARM-H, which is ~1000 fold more potent in gp120-binding and MT-2 antiviral assays than our previously reported derivative. Furthermore, computational analysis, taken together with experimental data, provides evidence that azain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…In 4TVP compound 1 is inserted into a small cavity decorated by P206, K207, V208, S209, F210, R304, G379, I439, and Q440, stabilized only by hydrophobic and van der Waals contacts. Interestingly, of the residues in this backside binding site, F210 forms a small hydrophobic accessory pocket in the CD4 bound conformation of gp120 where the BMS compounds should likely access when the gate-keeper residues W112 and F382 are open; 36 R304 is part of the V3 loop and I439 and Q440 are part of the V5 loop. It is worth noting that for 2, which differs from the parent compound 1 only in (i) the addition of a fluorine ortho to the chlorine on the region I phenyl and (ii) an N -methyl group at region III, no docking poses on the 4TVP back-side were generated.…”
Section: Resultsmentioning
confidence: 99%
“…In 4TVP compound 1 is inserted into a small cavity decorated by P206, K207, V208, S209, F210, R304, G379, I439, and Q440, stabilized only by hydrophobic and van der Waals contacts. Interestingly, of the residues in this backside binding site, F210 forms a small hydrophobic accessory pocket in the CD4 bound conformation of gp120 where the BMS compounds should likely access when the gate-keeper residues W112 and F382 are open; 36 R304 is part of the V3 loop and I439 and Q440 are part of the V5 loop. It is worth noting that for 2, which differs from the parent compound 1 only in (i) the addition of a fluorine ortho to the chlorine on the region I phenyl and (ii) an N -methyl group at region III, no docking poses on the 4TVP back-side were generated.…”
Section: Resultsmentioning
confidence: 99%
“…38 This priming action of BMS compounds was attributed mainly to interaction with the inner domain layer 2 α 1 helix. 38 Parker et al 40 reported a putative site on gp120 for BMS compounds, that is composed of a hydrophobic cavity in the inner domain gated by Trp112 and Phe382 and that could be accessible during the spontaneous conformational sampling of the Env trimer. 40 Interestingly, Langley et al 31 recently published a hypothetical mode of action for the BMS inhibitors by targeting a hydrophobic cleft in the unliganded Env gp120 where CD4 binding site is not formed (misfolded bridging sheet).…”
Section: Discussionmentioning
confidence: 99%
“…38 Parker et al 40 reported a putative site on gp120 for BMS compounds, that is composed of a hydrophobic cavity in the inner domain gated by Trp112 and Phe382 and that could be accessible during the spontaneous conformational sampling of the Env trimer. 40 Interestingly, Langley et al 31 recently published a hypothetical mode of action for the BMS inhibitors by targeting a hydrophobic cleft in the unliganded Env gp120 where CD4 binding site is not formed (misfolded bridging sheet). 31 In the current work, we also found that this exposed hydrophobic region appears to be targeted by the PT components.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, the same lab reported the structure‐guided optimization of ARMs targeting HIV gp120, which generated the advanced analogue 192 (derived from 193 ). This is ~1000‐fold more active in gp120‐binding and MT‐2‐based antiviral assays than 190 (Figure ) …”
Section: Exploitation Of Solvent‐exposed Regions For the Rational Desmentioning
confidence: 97%
“…This is~1000-fold more active in gp120-binding and MT-2-based antiviral assays than 190 ( Figure 28). 171 Prostate-specific membrane antigen (PSMA) is a membrane-bound glutamate carboxypeptidase expressed at high levels in many forms of prostate cancer and is thought to be an important target for the drug design of prostate carcinoma. A series of ARMs that enhance antibody-mediated immune recognition of prostate cancer cells was recently disclosed.…”
Section: Exploitation Of Solvent-exposed Regions For the Rational Dmentioning
confidence: 99%